Migraine associated with psychosocial factors such as catastrophizing, anxiety and stress - Santos, Erlene Roberta Ribeiro dos; Laurentino, Iris Milleyde da Silva; Leite, Antonio Flaudiano Bem; Andrade, Juliana Ramos de; Valença, Marcelo Moraes (Headache Medicine, 2025)
Introduction Migraine is a prevalent and disabling neurological disorder characterized by recurrent episodes of intense headache, often accompanied by nausea, photophobia, and phonophobia. Beyond its neurovascular and genetic nature, migraine is influenced by psychosocial factors that modulate symptom severity and frequency. Among these, pain catastrophizing, anxiety, and stress are highly relevant due to their impact on clinical outcomes and quality of life. This narrative review aims to synthesize the current literature on the influence of these psychosocial factors in migraine. Methodology This is a narrative literature review focused on the relationship between migraine and the psychosocial factors pain catastrophizing, anxiety, and stress. A search was conducted in the databases PubMed, Web of Science, and the Virtual Health Library (VHL) using the keywords: “catastrophizing” AND “anxiety” AND “migraine”. Results Pain catastrophizing is associated with increased pain intensity, reduced treatment response, and greater disability in individuals with migraine. Anxiety is a prevalent comorbidity that exacerbates symptoms through hyperactivation of limbic circuits. Stress acts as both a trigger and perpetuating factor, particularly in individuals with low adaptive capacity. These three factors interact dynamically, forming a biopsychosocial triad that contributes to migraine chronification and diminished quality of life. Conclusion Psychosocial variables significantly influence the course and burden of migraine. Their identification and management through integrative care strategies and public health initiatives are essential to improving clinical outcomes and reducing the societal impact of migraine.